2018
DOI: 10.1590/0001-3765201820170203
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of anurans from three mountain complexes in southeastern Brazil and their conservation implications

Abstract: Biogeographic tools support spatial distribution pattern hypotheses and help to determine priority areas for conservation. Our aim was to verify biogeographic patterns for anurans in three mountain complexes in southeastern Brazil, as well as to discuss the status of species conservation recorded and the biogeographical units evaluated. We selected 16 areas distributed in the Serra da Mantiqueira complex, south of Serra do Espinhaço and Serra da Canastra. We used the occurrence (geographic coordinates) of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Phantasmarana lutzae and Scinax dolloi are the only species recorded in our study that are currently known only from the state of Rio de Janeiro and are possibly endemic to the Itatiaia region (Frost 2021, Vittorazzi et al 2021, though Santos et al (2021) suggested that S. dolloi may occur more widely. Neves et al (2018) considered the Serra do Itatiaia as the area of highest amphibian endemicity rate within the Mantiqueira/Espinhaço/Canastra mountain complex in southeastern Brazil, with nine endemic anuran species (Scinax dolloi was not mentioned, possibly because it was a species of problematic identity at the time). Among the undescribed species recorded in the APA Serra da Mantiqueira survey, at least one, Ischnocnema sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phantasmarana lutzae and Scinax dolloi are the only species recorded in our study that are currently known only from the state of Rio de Janeiro and are possibly endemic to the Itatiaia region (Frost 2021, Vittorazzi et al 2021, though Santos et al (2021) suggested that S. dolloi may occur more widely. Neves et al (2018) considered the Serra do Itatiaia as the area of highest amphibian endemicity rate within the Mantiqueira/Espinhaço/Canastra mountain complex in southeastern Brazil, with nine endemic anuran species (Scinax dolloi was not mentioned, possibly because it was a species of problematic identity at the time). Among the undescribed species recorded in the APA Serra da Mantiqueira survey, at least one, Ischnocnema sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys have provided lists of amphibian species, mostly preliminary, for some high montane Atlantic Forest areas (i.e., above 1,000 m) in southeast Brazil (Cruz et al 2009, Siqueira et al 2011a,b, Garey et al 2014, Folly et al 2016, Lima et al 2021). These habitats are known for their high rates of endemism of anurans, particularly in portions of the Serra do Mar (Siqueira et al 2011b, Carvalho-e-Silva et al 2020 and Serra da Mantiqueira regions (Neves et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along the AF, the highlands, mostly in the central-southern portion, hold a remarkable diversity of anurans, considered important for maintaining taxonomic diversity and evolutionary history, with a great degree of endemism (Cruz & Feio 2007, Neves et al 2018, Silva et al 2018. This is primarily because of heterogeneous habitats and the floristics assemblages, altitudinal gradients and humidity in the region (Cruz & Feio 2007, Vasconcelos et al 2014).…”
Section: Introductionmentioning
confidence: 99%